Manajemen Organisasi tanpa Korupsi Perspektif QS. Al-‘Ashr (103): 1-3 - Nur Zazin; Galuh Nashrulloh Kartika MR (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This study tries to reveal on how The Qur’an Surah al-'Asr could be interpreted to describe the principles of behaviors required in managing organizations without corruption, what causes failure in organizing process, and an alternative solution for managing the organization to avoid corruption. This is a library research with the primary source taken from the Qur’an Surah Al-Ashr: 1-3, the secondary sources were taken from other verses that is related in the Qur'an, related hadith of the Prophet Muhammad and the books of tafsir, while the tertiary sources are taken from books or writings that have relevance to the problem of research. This qualitative research uses Tahlili interpretation approach with inductive and interpretative method. The results of this study shows that the success of an organization without corruption built on three principles of behaviors, they are to build a work ethic commitment to organize effectively and efficiently based on faith, to run the organization professionally, open to accept and provide truth-based criticism and patience. On the other hand, the cause of the failure to organize is not carrying out their obligations, unfairness that resulting in cheating, corruption and dishonest/hypocritical.